1979
DOI: 10.1093/infdis/139.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Investigations in Mice on the Potentiation of Resistance to Infections by a New Immunostimulant Compound

Abstract: BM 12.531, 2-[2-cyranaziridinyl-(1)]-2-[2-carbamoylaziridinyl-(1)]-propane, a new immunostimulant compound, increased the resistance of mice to infection with Candida albicans. Because BM 12.531 had no fungistatic activity in vitro, it is proposed that the therapeutic effect of BM 12.531 is caused by the stimulation of cell-mediated immunity. Administration of cyclophosphamide alone increased the mortality among mice infected with C. albicans and Pseudomonas aeruginosa, but when BM 12.531 was then administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The optimum dose of MDP(Ala) to stimulate nonspecific resistance to bacterial infection was relatively small when compared to that of other agents: e.g., for ubiquinone it is 25 mg/kg (8), and for BM 12.531, 50 mg/kg (6). The dose dependency of MDP in protective activity was demonstrated, although it was not strictly linear as reported for other immunopotentiators (8).…”
Section: Discussionmentioning
confidence: 83%
“…The optimum dose of MDP(Ala) to stimulate nonspecific resistance to bacterial infection was relatively small when compared to that of other agents: e.g., for ubiquinone it is 25 mg/kg (8), and for BM 12.531, 50 mg/kg (6). The dose dependency of MDP in protective activity was demonstrated, although it was not strictly linear as reported for other immunopotentiators (8).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the isohematinic acid-induced increased resistance of normal and compromised mice to the bacterial infections is presumed to be, at least in part, due to the enhancement of microbicidal activity of PMN and the induction of leucocytosis. In this respect, isohematinic acid is similar to BM 12,531 (4,5) in terms of its mode of action, although the structures of the two compounds are completely different. The effects of isohematinic acid and BM 12,531 were more pronounced in the compromised mice than in normal mice.…”
Section: Effects Of Isohematinic Acid and Bm 12531 On Nbt Reduction mentioning
confidence: 90%
“…BM 12,531, chemically synthesized as an immunomodulator, has been reported to stimulate immune responses including leucocytosis, phagocytosis, and lymphocyte blast formation (4,6,7). This agent also enhances the resistance of cyclophosphamide-treated mice to infections with Candida albicans and P. aeruginosa (5).…”
mentioning
confidence: 99%
“…Immunorestoration Test in Mice. The ability of novel carbocyclic MDP analogues to enhance nonspecific resistance to experimental fungal infection in immunosuppressed animals was examined in an immunorestoration test 43 in order to select a promising compound for further evaluation. It has already been reported that synthetic analogues of MDP increase nonspecific resistance to microbial infections mainly by exerting a priming effect on phagocytic cells leading to an enhancement in responses to the microbial challenge, such as microbi- cidal activity and release of cytokines.…”
Section: Chemistry N-{trans-2-[[2′-(acetylamino)cyclohexyl]-mentioning
confidence: 99%
“…Therefore, the survival increase of 3 animals in any group treated with a test substance, which was also usually obtained by azimexon as the positive control compound, was considered significant and possibly a result of immunorestorant activity. The results of the immunorestoration test for compounds 9a,b, 10a,b, 15a,b, and 21 as well as azimexon 43,50 and MDP as reference compounds are presented in Table 1. 2′-Acetylamino analogues 9a,b, 10a,b, and 11a-d which were available in diastereomerically pure forms were tested as single diastereomers, whereas other compounds were assessed as equimolar mixtures of two diastereomers (15a,b) or four diastereomers (21), respectively.…”
Section: Chemistry N-{trans-2-[[2′-(acetylamino)cyclohexyl]-mentioning
confidence: 99%